Popular Problems | Microsoft Math Solver (2024)

\frac { 5 x - 1 } { 5 } - \frac { 1 + x } { 2 } = 3 - \frac { x - 1 } { 4 } x \theta ^ { 6 } = f ( x ) = - 2 x ^ { 2 } + 8 x + 4 \frac { 3 } { 7 } 2 x ^ { 2 } + 3 x 793 \times 27 y = x ^ { 2 } \sqrt { \sqrt { ( \sqrt { x ^ { 2 } - 5 } ) ^ { 2 } } + 5 } ( 3 - 4 i ) - ( - 3 - 4 i ) x ^ { 2 } - 7 x + 12 \leq 0 \frac { 2 ^ { - 6 } m ^ { 13 } n ^ { 7 } } { 5 ^ { - 2 } m ^ { 7 } n ^ { 13 } } 10 \left| x-3 \right| =40 8 x + 5 = b x - 7 \left( \begin{array} { l } { 1 } \\ { 2 } \\ { 3 } \end{array} \right) + \left( \begin{array} { l } { 4 } \\ { 5 } \\ { 6 } \end{array} \right) \sqrt { e ^ { - i x } } ( \frac{ 28 }{ 48 } + \frac{ 24.5 }{ 50 } + \frac{ x }{ 48+52 } ) \times 0.1+ \frac{ 8 }{ 10 } \times 0.15+ \frac{ 15 }{ 30 } =0.5 \frac { 4 x ^ { 1 / 2 } } { 8 x ^ { 1 / 3 } } 21 m ^ { 3 } n ^ { 2 } + 3 mn ^ { 2 } - 6 mn ^ { 3 } + 9 m ^ { 2 } n ^ { 2 } = 10 \left| x-3 \right| > 40 a ^ { 3 } b ^ { 2 } , 7 a c ^ { 4 } , 14 b ^ { 2 } c ^ { 3 } - 2 x - 14 = - 2 x + 3 y + 71 + | x + 7 y + 19 | = 0 \lim_{ x \rightarrow 0 } \left( { x }^{ x } \right) 2 \cos 2 \theta + 1 = 0 ( x - 5 ) ^ { 2 } - 9 = 0 b ^ { 2 } - 4 b + 4 = 0 \left. \begin{array} { l } { \alpha ^ { 3 } + \beta ^ { 3 } } \\ { + \gamma ^ { 3 } = } \end{array} \right. \sqrt { 12 } + \sqrt { 75 } + \sqrt { 108 } = \sqrt { e ^ { - t x } } 3 ^ { 2 } \times 4 ^ { 2 } y = - 2 x ^ { 2 } - 8 x + 1 x + 4 y > 8 - 7 = 7 j + 28 | x + 3 y + 7 | + | x + 7 y + 19 | = 0 \left\{ \begin{array} { l } { x y = 1 } \\ { x + y = \frac { 3 \sqrt { 2 } } { 2 } } \end{array} \right. - 8 - 8 y = 6 - 2 y x - 2 x ^ { 2 } = 8 \left\{ \begin{array} { l } { x y = y } \\ { x + y = \frac { 3 \sqrt { 2 } } { 2 } } \end{array} \right. x ^ { 2 } + 3 x + 2 < 0 10 x - 5 x + 2 y - 2 y + x \log_{ 2 }({ 32 }) = x y = \frac { 2 } { 3 } x + 4 2 + 2 y + x + y ( { 9 }^{ 6 } 3 x + 2 x ^ { 2 } + 4 = x ( 2 x - 3 ) = 20 { \left( \frac{ 1 }{ 5 } \right) }^{ -1 } - { \left( \frac{ 1 }{ 7 } \right) }^{ -1 } l \frac { 9 } { 5 } z ( 5 z - 3 ) e ^ { 2 } + 2 T _ { 2 } = \frac { 1.520 mm \times 290 ^ { \circ } K } { 380 mm } x \sqrt { 2 x } \left. \begin{array} { c } { \frac { 3 } { 2 } a + b = 1 } \\ { a + \frac { b } { 2 } = 7 } \end{array} \right. \log ( 01 ) \left\{ \begin{array} { l } { 2 a x + b y = 14 } \\ { - 2 x + 9 y = - 19 } \end{array} \right. \frac { \sqrt { 2 x } } { x } 15 \times 8 q = \frac { K ( 2 ) ( 3 ) ^ { 2 } } { 8 } 2 x ^ { 2 } + 8 x - y + 8 = 0 ( - 2 ) ^ { 3 } \log ( 25 ) { 0.5 }^{ 3 } 2 x ^ { 2 } + 16 x + 24 \frac{\frac{8}{5}}{\frac{2}{25}-\frac{5}{16}} ( 38 ) = 56 - 14 \frac { 2 } { 3 } - 5 x = b x + \frac { 1 } { 3 } ( \frac{ 28 }{ 48 } + \frac{ 24.5 }{ 50 } \frac{ x }{ 48+52 } ) \times 0.1+ \frac{ 8 }{ 10 } \times 0.15+ \frac{ 15 }{ 30 } \times 0.75=0.5 \left. \begin{array} { l } { 3 - 3 y = -4 }\\ { \text{Solve for } z \text{ where} } \\ { z = -2 y } \end{array} \right. \log _ { e } 2 y = - 2 x ^ { 2 } - 8 x + 9 9 = \frac { K ( 2 ) ( 3 ) ^ { 2 } } { 8 } 18 \times 1 \div 20 g ^ { 1 } ( 3 ) - 5 x - x ( x + 2 ) ( x - 4 ) ( 4 x - 1 ) ^ { 2 } = ( x - 1 ) ( x + 1 ) 7 ^ { 3 } \cdot 16 ^ { - 9 } { x }^{ 2 } 4x+3=0 y = \tan ^ { - 1 } ( - 2 x ) x ^ { 2 } + x - 56 = 0 699 \times 533 \frac{3}{n^{2}}=\frac{n-4}{3 n^{2}}+\frac{2}{3 n^{2}} - 4 x + 60 < 72 - 2 x ^ { 2 } + 12 x - 14 > 0 ( 2 x + 5 ) ( 2 x + 3 ) 7 - 2 \times ( 3 x ) = 6 x - ( - 2 ) = 26 3 \cdot ( 1 + 3 ) ^ { 2 } + 2 ^ { 2 } + 2 ^ { 3 } 2x+ { x }^{ 2 } -4 { x }^{ 3 } \log _ { 7 } 1 - \log _ { 1 } 4 \frac { 2 } { 3 - 1 } \int \frac { d x } { x \sqrt { x + 1 } } f ( x ) = 340 ( 0.025 ) ^ { x } 64+81= \left. \begin{array} { l } { x - 3 = y } \\ { 4 x = 37 + 3 x } \end{array} \right. 4 \times 16 \{ [ ( 3 * Z ^ { 2 } ) ^ { 5 } ] ^ { 3 } \} ^ { 6 } ( u + 3 ) ( u - 6 ) \log ( 0.4 ) (43.3-x) { \left(x+7.35 \right) }^{ 2 } =27562.5 8 x ^ { 3 } + 5 + 7 x ^ { 2 } + 6 x ? {(e)^{ - \infty }} ( \frac{ 28+24.5+x }{ 48+50+48+52 } ) \times 0.1+ \frac{ 8 }{ 10 } \times 0.15+ \frac{ 15 }{ 30 } \times 0.75 > 0.5 2 \cos ^ { 2 } \theta + 9 \cos \theta + 4 = 0 ( 5 c + 3 ) ( 4 c - 7 ) f ( x ) = \frac { 1 } { 6 } x ^ { 3 } + \frac { 1 } { 2 } x ^ { 2 } - \frac { 15 } { 2 } x - \frac { 43 } { 6 } 2 + 2 y = \frac { 7 } { ( x ^ { 3 } - x ^ { 2 } + 7 x ) ^ { 5 } } ( x + y ) ^ { 2 } = 5 ( \frac { x ^ { 3 } y } { 4 } ) \div ( \frac { 4 } { x } \div \frac { 6 } { y ^ { 3 } } ) { 4 }^{ 4 } \sqrt { 1 - 2 ( x ^ { 2 } + 3 x ) } { x }^{ 2 } =y \sqrt { \frac { 5 } { 20 } } 59 - 7 ( 38 ) = 56 - 14 51 x ^ { 4 } + 3 x ^ { 2 } + x + 2 f ( x ) = a _ { 0 } ( 3 x ^ { 3 } + 11 x ^ { 2 } - x - 3 ) \div ( x ^ { 2 } + 4 x + 1 ) ( 0 ) 75 x - 25 f ( x ) = \int _ { 2 } ^ { x } ( \frac { 1 } { 2 } t ^ { 2 } - 1 ) ^ { 6 } d t x ^ { 2 } - 4 x - 5 = 0 a ^ { 3 } - 4 a ^ { 2 } + 2 a - 1 2 \cdot \sqrt[ 3 ] { - 125 } + 4 \cdot \sqrt[ 5 ] { 32 } - 6 \cdot \sqrt[ 3 ] { - 8 } - x - 2 - x - 2 (32 \sqrt{ 3 } ) \times 2 \frac{ 1 }{ 2 } x+x = \frac{ 51 }{ x } \frac { ( 3 x ^ { 2 } y ) ^ { - 1 } x ^ { 2 } z } { 3 y ^ { - 1 } } 7( \frac{ 11 }{ 20+7 } 3 < 2 x + 1 < 11 5 { x }^{ 2 } +12x-4 > 6 \int \sqrt { \tan ^ { 5 } x } \sec ^ { 4 } x d x = \left. \begin{array} { l } { A ^ {C} = B }\\ { \text{Solve for } a \text{ where} } \\ { a = C } \end{array} \right. 3 x + 2 x ^ { 2 } - x ^ { 3 } \frac{ x-120500 }{ x } = 0.02 5- { \left(x-4 \right) }^{ 2 } ( - 5 ) ^ { 3 } = 6.5 \times 4 19 \times 9 = \left. \begin{array} { l } { 3 t - 3 = 5 } \\ { 4 s - 37 = t } \end{array} \right. \lim _ { x \rightarrow 2 } \frac { \sqrt { x - 1 } - 1 } { \sqrt { x + 2 } - 2 } \lim _ { x \rightarrow 1 } \frac { \sqrt { x } - 1 } { x } ( n - 2 \sqrt { 2 } ) ( n + 2 \sqrt { 2 } ) 3 x = - \frac { 4 } { 3 } + \sqrt { 52 } = 1 f ( x ) = - 12.5 x ^ { 2 } + 1.375 x - 1.500 \frac{ 19 }{ 56 } - \frac{ 1 }{ 72 } - \frac{ 10 }{ 84 } + \frac{ 8 }{ 63 } == \frac { 1 } { 4 } { 8 }^{ \frac{ 2 }{ 3 } } 2 x - 5 = - 13 { \left( \frac{ 3 }{ 7 } \right) }^{ -2 } \theta = \frac { \sqrt { 3 } } { 2 } 5 ^ { - 1 } - \frac { 1 } { 2 } \int x \sqrt { 2 x + 1 } (15 \div 3.6)= ( n - 6 ) ( n - \frac { 1 } { 2 } ) { \left( \frac{ 15 }{ 3.6 } \right) }^{ 2 } 252 \cdot 3 38+2040000 \div 85000 a x ^ { 2 } + 3 x - 3 7 ( 4 x - 1 ) + 6 x > - 279 ? x ^ { 3 } y ^ { 4 } z ^ { 4 } , x ^ { 2 } y z ^ { 3 } , x ^ { 2 } y ^ { 2 } z ^ { 2 } y = - \frac{ 1 }{ 4 } -4 24 { x }^{ 2 } +16xy+8=84 2 ( y - 1 ) ^ { - 3 } + ( y + 3 ) = 5 ( y + 1 ) | - x ^ { 2 } + x - 1 | \leq 2 x + 5 x ^ { 2 } - 5 x + 3 y = 20 \frac { 2 } { 5 } \int{ x \sqrt{ 2x++1 } }d x \frac { 3 } { 4 } + \frac { 5 } { 6 } - \frac { 15 } { 12 } = 77 \div 4400 \left. \begin{array} { c } { x _ { 1 } + 2 x _ { 2 } - x _ { 3 } + 3 x _ { 4 } = 0 } \\ { 2 x _ { 1 } + 3 x _ { 2 } - x _ { 3 } + 2 x _ { 4 } = 0 } \\ { x _ { 1 } \quad + 3 x _ { 3 } + 3 x _ { 4 } = 0 } \end{array} \right. 949 - 2 = 3 x + 28 \leq 25 \left. \begin{array} { l } { \frac { x } { 3 } - \frac { y } { 2 } = 8 } \\ { \frac { x } { 5 } + \frac { y } { 3 } = 1 } \end{array} \right. [ \frac { ( f ^ { 3 } g ^ { - 8 } h ) ^ { 7 } } { ( g ^ { 5 } h ^ { - 3 } f ) ^ { - 8 } } ] ^ { 5 } 1 - \frac { x } { 4 } > 2 ( 1,53 \cdot 3 x-3+ \frac{ 4 }{ { x }^{ 2 } } =0 - x ^ { 2 } - x - 1 = 0 \frac{ 1 }{ 2 } \times \frac{ 5 }{ 4 } 949 \div 2 = ( 6 y ^ { 2 } - 8 y ^ { 3 } + 3 ) 7 y ^ { 5 } x ^ { 2 } - 3 x = y + 3 565 : 7 = x ^ { 2 } + 2 x - 15 \geq 0 \frac{ 2 }{ 5 } \times 3 \frac { 1 } { 9 } f ( x ) = \frac { 7 } { ( x ^ { 4 } - 5 x ^ { 3 } - 12 x ^ { 2 } + 36 x ) } ( + \frac { 1 } { 2 } ) + ( + \frac { 2 } { 3 } ) - ( - 1 \frac { 1 } { 6 } ) - 5 x ^ { 4 } y \frac { x - 2 } { 6 } \geq \frac { x - 1 } { 9 } + \frac { 7 } { 18 } ( + \frac { 1 } { 2 } ) - ( + \frac { 2 } { 3 } ) + ( - 1 \frac { 1 } { 6 } ) = \frac { 6 - x } { x - 2 } \leq \frac { 4 - x } { x + 2 } y = h ^ { - 1 } ( x ) 2 \cdot \pi ( \frac { x } { 2 } ) ^ { 2 } \cdot \sin ( x )
Popular Problems | Microsoft Math Solver (2024)
Top Articles
Latest Posts
Article information

Author: Horacio Brakus JD

Last Updated:

Views: 5978

Rating: 4 / 5 (71 voted)

Reviews: 94% of readers found this page helpful

Author information

Name: Horacio Brakus JD

Birthday: 1999-08-21

Address: Apt. 524 43384 Minnie Prairie, South Edda, MA 62804

Phone: +5931039998219

Job: Sales Strategist

Hobby: Sculling, Kitesurfing, Orienteering, Painting, Computer programming, Creative writing, Scuba diving

Introduction: My name is Horacio Brakus JD, I am a lively, splendid, jolly, vivacious, vast, cheerful, agreeable person who loves writing and wants to share my knowledge and understanding with you.